Comparison of Cardiovascular Status Between Pre- Induction Period and The Different Positions of Anaesthetized Patients in Laparoscopic Cholecystectomy (Journal of the Bangladesh Society of Anaesthesiologists, 2017)
The laparoscopic cholecystectomy nowadays is the method of choice for treatment of patients with cholelithiasis. This surgery involves different types of positioning of the anaesthetized patient. Our study was planned to compare the haemodynamic changes between the pre-induction period with the different positions of the anaesthetized patients during laparoscopic cholecystectomy. Thirty two (32) female patients of ASA physical status - 1 & 11, aged between 18 to 55 years, scheduled for elective laparoscopic cholecystectomy under general anesthesia, were enrolled in the study. All the patients were medicated with tablet clonazepam (0.5mg) on the night before surgery. On arrival to the operation theatre, baseline heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial blood pressure (MAP), and arterial oxygen saturation (SpO2) were recorded. The patients were then induced with Inj. propofol (1.5 to 2mg/kg). Endotracheal intubation was facilitated with Inj. vecuronium (0.1mg/kg). Anaesthesia was maintained with halothane 0.5% and nitrous oxide 60%, in oxygen. The propofol was infused to strengthen the maintenance of anaesthesia. During operation patient was monitored for HR, NIBP, ECG, ETCO2, and SpO2. The haemodynamic tools of the patients were continuously recorded. The pre-induction mean HR, SBP, DBP, MAP were compared with the values found after induction in trendelenburg and reverse trendelenburg position. The mean HR during pre-induction period & after induction in trendelenburg position, & reverse trendelenburg position were respectively 79.2±8.2, 76.6±9.6, and 70.1±5.9beats/min. The mean HR was statistically significant (p